Shikhara of the Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The shikhara (superstructure) of the Mandaleshwar Mahadev Temple is built in brick. It is in the shekhari (multi-spire) variety of Latina shikhara where the mulashringa (main spire) is complimented by many small shringas (spires) emanating from it. These half and miniature shringas provide a cascading effect to the shikhara. The mulashringa is styled as a Latina sikhara. It is made up of five bands, in which the central band is broad, flanked by two bands each on either side. These side bands are of equal size. The brick shikhara is likely to be a later addition to the temple.